First molecular phylogenetic and serological insights into Listeria monocytogenes infection in aborted ewes in Iraq: A cross-border comparative analysis - Luma F. M. Al-Ethafa; Ahmed Jassim Almialy; Hasanain A. J. Gharban; Isra’a M. Essa; Sattar R. S. Al-Eqabi (Veterinary World, 2025)
Background and Aim: Listeria monocytogenes is a significant zoonotic pathogen linked to reproductive losses in livestock and serious health risks in humans. In Iraq, listeriosis remains underreported in sheep, with limited data on its molecular and epidemiological characteristics. This study aimed to (1) estimate the seroprevalence of L. monocytogenes in recently aborted ewes, (2) evaluate the association between seropositivity and clinical indicators, and (3) perform molecular detection and phylogenetic analysis of polymerase chain reaction (PCR)-confirmed isolates.